Factors Associated with Vaginal Birth after Previous C-Section in Pregnant Women - Neelam Ansari, Aneela Habib, Shakira Perveen, Sana Shameer, Saima Ali, Sarah Kazi (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The cesarean delivery (CD) rate has increased significantly over recent decades. It is estimated that almost a third of women have delivered by CD worldwide. In most countries, the caesarean section rate (CSR) has exceeded the level of 10–15% recommended by the World Health Organization (WHO). In different areas of Pakistan current CSR was 16–20%, approximately. Objective: To determine the frequency of successful vaginal birth after previous cesarean section (VBAC) and factors associated with failed VBAC and fetomaternal outcome after trial of labour after cesarean section (TOLAC) in pregnant women. Study Design: This descriptive cross sectional study was conducted in the department of Obstetrics & Gynaecology of Civil Hospital Karachi for the duration of six months from July, 2020 to January, 2021. Subjects and Method: The pregnant women who had a prior cesarean delivery and the intension to desire a TOLAC at the prenatal visit at 36 weeks were recruited according to inclusion and exclusion criteria. Trail of labor was assessed of all women and the outcome of successful VBAC after attempted TOLAC was noted and associated factors. Results: Total numbers of patients included in study were 142. Out of which 97 (68.3%) had successful vaginal delivery after previous C-section and 45 (31.6%) were failed VBAC. Regarding the Factors associated with Successful VBAC in pregnant women, 83 (85.5%) had normal BMI, 94 (96.9%) had Gestational age b/w 37th to 40 weeks, 93 (95.8%) were booked cases, 51 (52.5%) were working women, 87 (89.6%) had h/o of VBAC, 81 (83.5%) had Interval time from previous CS > 18 months and 96 (98.9%) had normal birth weight Conclusion: Majority of the cases of previous CS done can be delivered safely by the vaginal route, without any major 3 complication to the mother and the newborn, in an institution having facilities for emergency CSs.